Application of Resource Utilization in Dementia (RUD) instrument in a global setting. Issue 4 (12th November 2012) - Wimo, Anders; Gustavsson, Anders; Jönsson, Linus; Winblad, Bengt; Hsu, Ming‐Ann; Gannon, Brenda
Abstract: Background: The Resource Utilization in Dementia (RUD) questionnaire is the most widely used instrument for resource use data collection in dementia, enabling comparison of costs of care across countries with differing health care provisions. Recent feedback from payers questioned its face validity given that health care provisions have changed since the initial development of the RUD in 1998. The aim of this study was to update the RUD to improve its face validity in Alzheimer's disease (AD) clinical research and its utility for health care resource allocation. Methods: An extensive PubMed review was conducted of current relevant resource items in AD in 15 countries. The findings were complemented by interviews with local care providers and experts in dementia care and health economics. Their proposed revisions were discussed with five leading dementia experts in North and South America, northern and southern Europe, and Asia. A new version of the RUD was developed based on their recommendations. Results: RUD users identified a need for more information relevant to coverage decisions. Proposed revisions included changes to existing questions (e.g., to capture more accurately the number and type of health care visits) and the addition of new questions (e.g., on informal caregiver hours and the primary caregiver's hours of sleep). Conclusion: Several minor changes were made to the RUD instrument to improve the accuracy and precision of the data while maintaining comparability with the original version and reflecting current medical practice. The RUD Complete Version 4.0 is now available for use in future AD clinical trials.